Chemostratigraphic trends and provenance of the Permian Tanqua and Laingsburg depocentres, southwestern Karoo Basin, South Africa - Van Lente, Belinda (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2004.